Antibiotic point prevalence survey and antimicrobial resistance in hospitalized patients across Peruvian reference hospitals - Claudia Rondon; Coralith Garcia; Fiorella Krapp; Isela Machaca; Marco Olivera; Victor Fernández; Miguel Villegas; Pierina Vilcapoma; Martin Casapia; Fátima Concha-Velasco; Juan C. Díaz; Favio Sarmiento; et al. (Journal of Infection and Public Health, 2023)
Background: Peru reports higher levels than other countries in Latin America of resistance to antimicrobials among Gram-positive and Gram-negative bacteria, however data on antibiotic use in Peru are scarce. This study aims to estimate the prevalence and quality of antibiotic prescription in hospitalized patients and to determine the antibiotic susceptibility rates of bacteria causing key bacterial infections. Methods: We carried out a point prevalence survey of antibiotic prescription at ten public hospitals in nine regions of Peru. Data was collected from patients hospitalized during a 3-week period, with details about antibiotic use, patient information, and antimicrobial susceptibility. Results: 1620 patient charts were reviewed; in 924 cases antibiotics were prescribed (57.0 %, range 45.9–78.9 %). Most of the antibiotics (74.2 %) were prescribed as empirical treatment, only 4.4 % as targeted treatment. For 9.5 % of cases the reason for antibiotic use was unknown. Cephalosporins were the most prescribed (30.0 %), followed by carbapenems (11.3 %). Ninety-four blood cultures were positive for bacterial growth, 48.8 % of the Staphylococcus aureus were methicillin-resistant, among Escherichia coli and Klebsiella pneumoniae, 51.7 % and 72.7 % were resistant to third-generation cephalosporins (3GC), 3.4 % and 18.2 % were resistant to carbapenems, respectively. Among bacteria isolated from urine cultures (n = 639), 43.9 % of E. coli and 49.2 % of K. pneumoniae were resistant to 3GC, and 0.9 % of E. coli and 3.2 % of K. pneumoniae were resistant to meropenem. Conclusions: The overall proportion of hospitalized patients receiving antibiotics in hospitals from different regions in Peru was high, with only a small proportion receiving targeted treatment. Cephalosporins and carbapenems were the most frequently prescribed antibiotics, reflecting high resistance rates against 3GC and carbapenems in Enterobacterales isolated from blood and urine.